Virtual Machine Server For SAP 4HANA Cloud Print Manager - Haryadi, Eko; Wijayanti, Diah; Widyastuti, Indria; Mustomi, Dede (Universitas Islam Kuantan Singingi, 2022)
Enterprise resource planning (ERP) requires supporting facilities to be able to make a major contribution to the user or company. One of the widely used ERP is SAP. The cloud based version of SAP is S4hana. This paper explains how S4hana provides a solution by mass printing on the S4hana side and the print results will be displayed on the server side. The method used is by using the System development life cycle (SDLC) on the development side of the virtual server and using the SAP active method when implementing or migrating the system to a new system. The final result is the interaction process between S4hana and the virtual machine and then the user will get mass printouts stored in the public folder